Applications of variable thermal properties in Carreau material with ion slip and Hall forces towards cone using a non-Fourier approach via FE-method and mesh-free study - Nazir, Umar; Sohail, Muhammad; Mukdasai, Kanit; Singh, Abha; Alahmadi, Reham A.; Galal, Ahmed M.; Eldin, Sayed M. (Frontiers in Materials, 2022)
This research highlight the utilization of two viscosity models to study the involvement of variable properties for heat and momentum transport in rotating Carreau fluid past over a cone. The rheology of Carreau material is carried out by variable dynamic viscosity over heating cone. The transport of momentum phenomenon is modeled by considering generalized Ohm law in Carreau liquid and thermal transport in derived by considering variable thermal conductivity, heat flux model. The considered model is derived in the form of nonlinear PDEs with boundary layer analysis. The nonlinear PDEs are converted into coupled ODEs by using approximate transformation and converted equations are solved numerically by finite element methodology. The impact of numerous parameters is displayed graphically and their behavior is discussed in detail.